CDK phosphorylation of TRF2 controls t-loop dynamics during the cell cycle - Sarek, Grzegorz (Nature, 2019)
Telomere end-protection by the shelterin complex prevents DNA damage signalling and promiscuous repair at chromosome ends. Evidence suggests that the 3’ single-stranded telomere end can assemble into a lasso-like t-loop configuration(1,2), which has been proposed to safeguard chromosome ends from being recognized as DNA double strand breaks(2). Mechanisms must also exist to transiently disassemble t-loops to allow faithful telomere replication and to permit telomerase access to the 3’-end to solve the end replication problem. However, the regulation and physiological importance of t-loops in end-protection remains uncertain. Here, we identify a CDK phosphorylation site in the shelterin subunit, TRF2 (Ser365), whose dephosphorylation in S-phase by the PP6C/R3 phosphatase provides a narrow window during which the helicase RTEL1 is able to transiently access and unwind t-loops to facilitate telomere replication. Re-phosphorylation of TRF2 on Ser365 outside of S-phase is required to release RTEL1 from telomeres, which not only protects t-loops from promiscuous unwinding and inappropriate ATM activation, but also counteracts replication conflicts at DNA secondary structures arising within telomeres and across the genome. Hence, a phospho-switch in TRF2 coordinates assembly and disassembly of t-loops during the cell cycle, which protects telomeres from replication stress and an unscheduled DNA damage response.